n-3 PUFAs enhance the frequency of murine B-cell subsets and restore the impairment of antibody production to a T-independent antigen in obesity[S] - Heather Teague; Cassie J. Fhaner; Mitchel Harris; David M. Duriancik; Gavin E. Reid; Saame Raza Shaikh (Journal of Lipid Research, 2013)
The role of n-3 polyunsaturated fatty acids (PUFA) on in vivo B-cell immunity is unknown. We first investigated how n-3 PUFAs impacted in vivo B-cell phenotypes and antibody production in the absence and presence of antigen compared with a control diet. Lean mice consuming n-3 PUFAs for 4 weeks displayed increased percentage and frequency of splenic transitional 1 B cells. Upon stimulation with trinitrophenylated-lipopolysaccharide, n-3 PUFAs increased the number of splenic transitional 1/2, follicular, premarginal, and marginal zone B cells. n-3 PUFAs also increased surface, but not circulating, IgM. We next tested the effects of n-3 PUFAs in a model of obesity that is associated with suppressed humoral immunity. An obesogenic diet after ten weeks of feeding, relative to a lean control, had no effect on the frequency of B cells but lowered circulating IgM upon antigen stimulation. Administration of n-3 PUFAs to lean and obese mice increased the percentage and/or frequency of transitional 1 and marginal zone B cells. Furthermore, n-3 PUFAs in lean and obese mice increased circulating IgM relative to controls. Altogether, the data show n-3 PUFAs enhance B cell-mediated immunity in vivo, which has implications for immunocompromised populations, such as the obese.